Almost the perfect murder : the killing of Elaine O'Hara, the extraordinary Garda investigation and the trial that stunned the nation : the only complete inside account /: the killing of Elaine O'Hara, the extraordinary Garda investigation and the trial that stunned the nation : the only complete inside account. (2015) - Williams, Paul, 1964-
No abstract available